Statistical analysis of notational AFL data using continuous time Markov chains - Meyer, D.; Forbes, D.; Clarke, S. R. (Journal of Sports Science & Medicine, 2006)
Animal biologists commonly use continuous time Markov chain models to describe patterns of animal behaviour. In this paper we consider the use of these models for describing AFL football. In particular we test the assumptions for continuous time Markov chain models (CTMCs), with time, distance and speed values associated with each transition. Using a simple event categorisation it is found that a semi-Markov chain model is appropriate for this data. This validates the use of Markov Chains for future studies in which the outcomes of AFL matches are simulated.